Strategy Media Print Banten Raya Maintaining Its Existence Amid The Dominance of Social Media - Vivi Isri Undayah; Rizqi Fitrianti; Arfian Suryasuciramdhan; H. Achmad Nashrudin Priatna; Hj. Putri Handayani (International Journal of Science and Environment (IJSE), 2025)
The development of digital technology has had a significant impact on the media industry landscape, particularly local print media. This study aims to analyze the media convergence strategies implemented by Banten Raya print media in their efforts to maintain their existence amidst the dominance of social media. This study also examines the challenges and obstacles faced by Banten Raya print media in responding to changes in public information consumption behavior. The approach used in this research was a qualitative case study. Data collection techniques included in-depth interviews, observation, and documentation of Banten Raya editorial staff. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The research results show that Banten Raya implemented a convergence strategy through three aspects: (1) content distribution to various platforms with differentiation of writing styles (formal-in-depth for print, light-efficient for online, casual for social media), (2) collaboration with Citizen Journalism and local information accounts and the development of community columns, and (3) adaptation to the migration of cross-generational audiences who prefer digital platforms. The main challenges include limited human resources with the burden of multitasking journalists, obstacles to adapting to technology in news verification, differences in time management between platforms, and difficulties in producing social media content. The convergence strategy succeeded in creating value differentiation: digital excels in the speed of breaking news, print provides in-depth analysis, and collaboration increases public awareness of local issues. The research confirms that media convergence is a comprehensive transformation in organizational structure, workflow, and collaborative culture, providing practical contributions for local print media in designing survival strategies through platform differentiation and continuous adaptation.